2011
DOI: 10.17221/47/2010-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of SSR markers for determining the origin of melon plantlets derived through unfertilized ovary culture

Abstract: Malik A.A., Li Cui, Shuxia Zhang, Jin-feng Chen, 2011. Efficiency of SSR markers for determining the origin of melon plantlets derived through unfertilized ovary culture. Hort. Sci. (Prague), 38: 27-34.The effects of temperature pre-treatment, thidiazuron, naphthaleneacetic acid, and 6-benzylaminopurine on in vitro gynogenic plant production from un-pollinated melon (Cucumis melo L.) ovaries were investigated. Simple sequence repeat (SSR) marker analysis was conducted to identify the homozygous diploid individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…It is interesting to note that both I1 and I2 contained TDZ as growth regulators either singly or in combination with BA. TDZ has been frequently reported as the most efficient growth regulator for gynogenesis induction in cucurbit crops (Gémes-Juhász et al, 2002;Suprunova and Shmykova, 2008;Diao et al, 2009;Malik et al, 2011;Li et al, 2013). The percentages of ELS formation obtained With two different Chinese cucumber inbred lines, the highest embryo induction frequencies (11.1-12.1%) were achieved using 0.07 mg/L TDZ (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…It is interesting to note that both I1 and I2 contained TDZ as growth regulators either singly or in combination with BA. TDZ has been frequently reported as the most efficient growth regulator for gynogenesis induction in cucurbit crops (Gémes-Juhász et al, 2002;Suprunova and Shmykova, 2008;Diao et al, 2009;Malik et al, 2011;Li et al, 2013). The percentages of ELS formation obtained With two different Chinese cucumber inbred lines, the highest embryo induction frequencies (11.1-12.1%) were achieved using 0.07 mg/L TDZ (Li et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…Culture medium is a principal factor in controlling the gynogenesis in vitro, and culture media component formulation likewise contributes to the progress of gynogenic methods. The modified medium is the changeable of organic nitrogen and carbohydrates.The preliminary study has reported that the microelements, macroelements and organic elements affect the embryoid induction of cucumber, and vitamins and glycine were considered to promote the ovule enlargement (Malik et al 2011;Min et al 2016;Moqbeli et al 2013;Rakha et al 2012;Zhan et al 2009). In the present study, we first screened the appropriate medium for ovule enlargement of watermelon, the results revealed that M2 medium, which brimmed with organic matter, was appropriate for ovule enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Further, induction medium without TDZ or at excessive TDZ concentration often lead to low outcomes of embryos in vitro (Diao et al 2009;Malik et al 2011;Moqbeli et al 2013). In the present study, the concentrations of TDZ, NAA, BA and KT affect ovule enlargement, among which, TDZ and BA showed best effect on ovule enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The uniformity of these progenies tested may indicate that the octoploid plant was derived only by spontaneous doubling of the haploid gametes in vitro instead of deriving from any somatic tissues of the female organs such as ovary/ovule wall or any other part of the floret organs. Further study on the zygosity of the tetraploid tef lines using modern molecular technique such as simple sequence repeat (SSR) (Malik et al, 2011) could reveal whether spontaneous chromosome doubling and production of homozygous lines were achieved through Figure 2. Microscopic examination of the R0 lines for male sterility mutants: a) normal pistils and anthers growth of the control plant at anthesis stage compared to the smallest size of di-haploids (b) and the vigor octoploid (c) with variant color (whitish) indicating male sterile anther and herkogamous, incompatibility (physical barrier; short filament of the matured anthers with the fully receptive stigmas d) fertile anther of the control plant, filled with pollen grains e) viable normal fertile pollen grains isolated from matured anthers, larger green (fertile) and smaller and darker (arrows, none fertile) f) deformed pollen grains of the di-haploid anther g) shriveled anther of the mutant line with few or no pollen grains h) pollinated stigma with un functional pollen grains unable to germinate on the receptive stigma i) fully sterile matured spikelet of the di-haploid j) fully sterile, matured, spikelet of the mutant tetraploid DH k) partially fertile tetaploids R0.…”
Section: Discussionmentioning
confidence: 99%